PENGEMBANGAN MODEL PEMBELAJARAN SEPAK BOLA MELALUI PERMAINAN FOOTBALL SOCCER GACONE PADA SISWA KELAS VIII SMP NEGERI 5 TANAH SEPENGGAL - Deddy Rahmat Saputra (Jurnal Muara Olahraga, 2022)
The background of this research is the lack of realm of developing physical research is the lack of realm of developing physical education learning models. The problem in this study is how the modified form of the soccer game is suitable for the VIII grade students of SMP Negeri 5 Tanah Sepenggal. This research method is development research that refers to the modified Borg & Gall development model, namely: (1) conducting preliminary research and gathering information, including field observations and literature review, (2) developing the initial product form (in the form of game activities soccer) (3) expert evaluation using one physical education expert and one learning expert, as small-scale trials, using an evaluation sheet which was then analyzed, (4) the first product revision based on the results of expert evaluations and small-scale trials, (5) large-scale trials, (6) revision of the final product, (7) the final result of the modification of the learning game “Football Soccer Gacone”. The research data are in the form of product quality, suggestions for product improvement, and the results of filling out questionnaires by students. Data was collected using expert evaluation sheets (one physical education expert and one learning expert), small-scale trials (8 students ), and large-scale tests (30 students). The data analysis technique used is the descriptive percentage to reveal students' cognitive, affective, and psychomotor aspects after using the product. From the test results obtained expert evaluation data, namely Physical Education experts 89% (good), Learning experts 86% (good), small-scale trials 75,83% (good), and large-scale trials 69,66% (good enough). From the existing data, it can be concluded that the development of physical education learning through the Football Soccer Gacone game can be used in the physical education learning process for junior high school students. Based on the results of research and discussion, it can be concluded that the Football Soccer Gacone game is effective, so it can be school students. Based on the results of research and discussion, it can be concluded that the Football Soccer Gacone game is effective, so it can be applied as a learning model in physical education teachers at the 5 Tanah Spenggal Junior High School can use the Football Soccer Gacone Game model product in the physical education learning process.